1999
DOI: 10.1038/sj.bjc.6690320
|View full text |Cite
|
Sign up to set email alerts
|

DCC expression is related to mucinous differentiation but not changes in expression of p21WAF1/Cip1 and p27Kip1, apoptosis, cell proliferation and human papillomavirus infection in uterine cervical adenocarcinomas

Abstract: To clarify possible roles of DCC expression in tumour differentiation and cell kinetics, we immunohistochemically investigated 80 uterine cervical adenocarcinomas (C-ACs), including 31 mucinous (M) and 31 endometrioid (E) lesions, and 18 adenocarcinomas in situ (AIS), along with 39 normal cervical samples. The results were compared with findings for p21 WAF1/Cip1 and p27 Kip1 expression, apoptosis, cell proliferation and human papillomavirus (HPV) infection. Nine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Weak immunostaining was mainly detected in mucinous and adenosquamous carcinomas (Milde‐Langosch et al, 2001d). This is in accordance with Saegusa et al who found higher p27 scores in endometrioid than in mucinous AC (Saegusa and Okayasu, 1999). While we and others did not observe an association of p27 expression with HPV infection rate, we found a significant correlation of p27 levels with HPV 16/18 E6/E7 oncogene expression (Milde‐Langosch et al, 2001d).…”
Section: Cervical Carcinomacontrasting
confidence: 82%
See 2 more Smart Citations
“…Weak immunostaining was mainly detected in mucinous and adenosquamous carcinomas (Milde‐Langosch et al, 2001d). This is in accordance with Saegusa et al who found higher p27 scores in endometrioid than in mucinous AC (Saegusa and Okayasu, 1999). While we and others did not observe an association of p27 expression with HPV infection rate, we found a significant correlation of p27 levels with HPV 16/18 E6/E7 oncogene expression (Milde‐Langosch et al, 2001d).…”
Section: Cervical Carcinomacontrasting
confidence: 82%
“…Most studies described above dealed with squamous cervical lesions and only a minority of AC were examined. The few reports on AC agree in that they describe nuclear p27KIP1 immunoreactivity in a high percentage of invasive AC as well as ACIS (Lu et al, 1998,1999; Saegusa and Okayasu, 1999; Milde‐Langosch et al, 2001d). In our own study, p27 staining was observed in all analyzed AC with varying staining intensities and different proportions of positive tumor cells.…”
Section: Cervical Carcinomamentioning
confidence: 89%
See 1 more Smart Citation
“…Although the incidence of SCC has declined, adenocarcinoma (AC), which accounts for approximately 10 to 30% of cervical carcinomas, has remained the same or increased in some countries (6)(7)(8)(9)(10). Some studies have also shown a high incidence of HPV in AC (43.8-94%) and adenocarcinoma in situ (56.3-100%) (11)(12)(13)(14)(15).…”
mentioning
confidence: 94%
“…Positive control sections known to contain p21 or p53, respectively, were used (Saegusa and Okayasu 1999;Saegusa et al 2000). For p27 and two hormone receptors, stromal components or infiltrating lymphocytes were applied as internal controls.…”
Section: Immunohistochemistrymentioning
confidence: 99%